2003
DOI: 10.1055/s-2003-40351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Neomycin Analogs to Investigate Aminoglycoside-RNA Interactions

Abstract: A series of novel aminoglycoside oligosaccharide analogs containing a 2,5-dideoxystreptamine core scaffold was prepared to study aminoglycoside binding to the small subunit of 16S rRNA. A set of monosaccharide building blocks carrying amino groups in different positions and conformations around the pyranose ring was utilized in the assembly of oligosaccharides. These aminoglycoside analogs were analyzed for their RNA-binding capacity using a high throughput mass spectroscopy assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Thus, solvent combinations of water, MeOH, t-BuOH, CH 2 Cl 2 , toluene, pyridine, and CH 3 CN were found to have a distinct influence on the reaction. 25,257,464,467 As a testament to its synthetic utility, the diazotransfer reaction has been employed in the synthesis of biologically important targets including heparan sulfate fragments, 466 aminoglycoside antibiotics, 464 neomycin analogues, 468 heparin fragments, 461,463 hyaluronan neoglycopolymers, 460 and N-acetylneuraminic acid 257 derivatives. An alternative synthesis of 2-azido-2-deoxy derivatives from D D-glucosamine was reported by Dasgupta and Garegg.…”
Section: 22mentioning
confidence: 99%
“…Thus, solvent combinations of water, MeOH, t-BuOH, CH 2 Cl 2 , toluene, pyridine, and CH 3 CN were found to have a distinct influence on the reaction. 25,257,464,467 As a testament to its synthetic utility, the diazotransfer reaction has been employed in the synthesis of biologically important targets including heparan sulfate fragments, 466 aminoglycoside antibiotics, 464 neomycin analogues, 468 heparin fragments, 461,463 hyaluronan neoglycopolymers, 460 and N-acetylneuraminic acid 257 derivatives. An alternative synthesis of 2-azido-2-deoxy derivatives from D D-glucosamine was reported by Dasgupta and Garegg.…”
Section: 22mentioning
confidence: 99%
“…MS-based assays have also been used in a relatively high throughput fashion for affinitybased screenings of compounds against a 27-mer nucleotide RNA, an essential components of 16S rRNA A-site, which is responsible for binding of tRNA in translation [44,45]. Furthermore, these assays have helped to generate lead compounds that target ribosomal RNA, using structure-activity relations developed on the basis of binding affinities of known antibiotics to rRNA [46][47][48][49][50]. The perspective of MS as a drug discovery platform against RNA targets has been comprehensively reviewed [51].…”
Section: Direct Detection Of Non-covalent Macromolecule-ligand Complexesmentioning
confidence: 99%
“…However, it was found that the use of aluminum azide in THF leads to the desired 1,3-azido isomer 165 , albeit in low yield (18%) . Most recently, it was reported that the 1,3-diazido analogue 165 can also be obtained by reaction of compound 164 with triflyl azide (89% yield) . It has also been reported that opening of bisepoxide 162 in neat benzylamine proceeds with complete 1,3-regioselectivity to amino alcohol 166 …”
Section: 4 Dideoxystreptaminesmentioning
confidence: 99%